MENINGKATKAN KEMAMPUAN BERCERITA MELALUI KEGIATAN MENGGGAMBAR BEBAS DI KELOMPOK B TK MUSLIMAT WASILATUS SA’ADAH MANGUNREJO- KEPANJEN KAB. MALANG - Dwi Setyowati, Yenita; Ayu Asmah; Rina Wijayanti (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to understand how to improve storytelling ability in group B children through free drawing activities at the Muslimat Kindergarten (TKM) Wasilatus Sa'adah Kepanjen. Used in this study is a class action method with a qualitative descriptive approach. The research subjects were children aged 5-6 years with a total of 15 children. Data collection techniques were carried out through observation, interviews, and documentation. The findings showed that children's storytelling ability increased marked by indicators of children being able to express their ideas or feelings through pictures and being able to tell the story of the picture. At first, the level of children's storytelling ability was at 33%. After the action in cycle I, there was an increase to 65%, and after continuing to cycle II, the ability increased again to 86%. Looking at the development of cycles I and II, it can be concluded that free drawing activities can improve the storytelling ability of children 5-6 years old at TKM Wasilatus Sa'adah Kepanjen Keywords:  early childhood; storytelling; free drawing